2019
DOI: 10.1007/s00415-019-09401-1
|View full text |Cite
|
Sign up to set email alerts
|

Forced vital capacity and cross-domain late-onset Pompe disease outcomes: an individual patient-level data meta-analysis

Abstract: Background Late-onset Pompe disease (LOPD) is a rare, metabolic disease primarily affecting the musculoskeletal and respiratory systems. Forced vital capacity (FVC) is commonly used to measure pulmonary function; however, associations between FVC and other LOPD outcomes remain unclear. Methods A systematic literature review was conducted on November 2015, updated September 2016 and supplemented with clinical trial data from the sponsor. Outcomes included: 6-min walk tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 28 publications
0
17
0
3
Order By: Relevance
“…We obtained forced vital capacity (FVC), both seated and lying down, using the Carefusion Microlab ML 3500 MK8 spirometer (Carefusion, Yorba Linda, CA, USA). These last two tests were added due their being commonly used in Pompe disease patients to measure their clinical status ( 9 ). Finally, Creatine kinase levels in serum were quantified in the HSCSP biochemistry laboratory following standard protocols.…”
Section: Methodsmentioning
confidence: 99%
“…We obtained forced vital capacity (FVC), both seated and lying down, using the Carefusion Microlab ML 3500 MK8 spirometer (Carefusion, Yorba Linda, CA, USA). These last two tests were added due their being commonly used in Pompe disease patients to measure their clinical status ( 9 ). Finally, Creatine kinase levels in serum were quantified in the HSCSP biochemistry laboratory following standard protocols.…”
Section: Methodsmentioning
confidence: 99%
“…In an earlier study from our own group we had already reported the positive associations between participation in daily life (RHS) and the FVC and MRC [28]. Positive associations of the physical component of quality of life (PCS) with both FVC upright and the MRC were also described in an international meta-analysis [29]. This study corroborates the present results, as the individual level data used in the international study did not include the Dutch patients included in the present study.…”
Section: Discussionmentioning
confidence: 89%
“…In an earlier study from our own group we had already reported the positive associations between participation in daily life (RHS) and the FVC and MRC (31). Positive associations of the physical component of quality of life (PCS) with both FVC upright and the MRC were also described in an international meta-analysis (32). This study corroborates the present results, as the individual level data used in the international study did not include the Dutch patients included in the present study.…”
Section: Discussionmentioning
confidence: 89%